RETRACTED: Modeling Brain Somatic Mosaicism With Cerebral Organoids, Including a Note on Mutant Microglia - Verheijen, Bert M. (Frontiers in Molecular Neuroscience, 2019)
The brain is a genomic mosaic. Cell-to-cell genomic differences, which are the result of somatic mutations during development and aging, contribute to cellular diversity in the nervous system. This genomic diversity has important implications for nervous system development, function, and disease. Brain somatic mosaicism might contribute to individualized behavioral phenotypes and has been associated with several neuropsychiatric and neurodegenerative disorders. Therefore, understanding the causes and consequences of somatic mosaicism in neural circuits is of great interest. Recent advances in 3D cell culture technology have provided new means to study human organ development and various human pathologies in vitro. Cerebral organoids (“mini-brains”) are pluripotent stem cell-derived 3D culture systems that recapitulate, to some extent, the developmental processes and organization of the developing human brain. Here, I discuss the application of these neural organoids for modeling brain somatic mosaicism in a lab dish. Special emphasis is given to the potential role of microglial mutations in the pathogenesis of neurodegenerative diseases.